Memoria operativa y su incidencia en el aprendizaje de los estudiantes de quinto año educación general básica de la unidad educativa Delfos durante el período lectivo 2018 - 2019 - Bravo Lozano, Ruth Noemí (2019)
It has been considered pertinent to carry out this work because it consists of knowing the flaws that exist in learning due to the lack of stimulation of the operational memory of “DELFOS” Elementary School of 5th grade students since the subject dealt with it is of little knowledge for teachers and parents. The aim of this study is to analyze the incidence of operational memory in learning, for which it has been decided to choose certain theoretical and empirical methods such as analysis, synthesis, deduction and induction, as well as test application, surveys and interviews. The results obtained revealed that there are deficiencies in the reasoning of the students, this leads to individuals having difficulties in learning and as a consequence a low school performance…..